DAMPAK KONVERSI MINYAK TANAH KE GAS LPJ 3 KG TERHADAP PENDAPATAN UMK DI KOTA JAMBI - Sayid Syekh (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
The aim in this study was to look at the impact of the conversion of kerosene to LPG 3 kg to revenues MSEs in Jambi in this study looks Percentage number of small and medium industrial enterprises in the city of Jambi in 2014, reaching 2.66%, while the percentage of traders in Jambi reached 59.16% Percentage of graduates of junior high school education reached 22, 81% while university graduates whereas 19.04%. The impact of the conversion of kerosene to LPG 3 kg for MSEs in Jambi have a significant impact is shown where th = 3.33> t1% = 2,763 means the impact on SMEs of income change in Jambi.Keyword : the impact of the conversion, revenue